2022
DOI: 10.1136/thoraxjnl-2021-218563
|View full text |Cite
|
Sign up to set email alerts
|

Cluster analysis of transcriptomic datasets to identify endotypes of idiopathic pulmonary fibrosis

Abstract: BackgroundConsiderable clinical heterogeneity in idiopathic pulmonary fibrosis (IPF) suggests the existence of multiple disease endotypes. Identifying these endotypes would improve our understanding of the pathogenesis of IPF and could allow for a biomarker-driven personalised medicine approach. We aimed to identify clinically distinct groups of patients with IPF that could represent distinct disease endotypes.MethodsWe co-normalised, pooled and clustered three publicly available blood transcriptomic datasets … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Kraven et al 45 have recently taken a similar approach to our study, although there are several limitations that we believe are solved by our present study. Kraven et al combine several datasets to form a larger IPF dataset, but do so combining different tissue types.…”
Section: Discussionmentioning
confidence: 91%
“…Kraven et al 45 have recently taken a similar approach to our study, although there are several limitations that we believe are solved by our present study. Kraven et al combine several datasets to form a larger IPF dataset, but do so combining different tissue types.…”
Section: Discussionmentioning
confidence: 91%
“…One strategy for improving the performance of clinical trials in IPF is to move away from the “one disease, one drug” approach and instead embrace the principle of causative molecular mechanisms, generally referred to as “endotypes.” Identification of endotypes has the potential to explain disease heterogeneity, thus enabling treatment tailored to the individual patient. Recently, Kraven and colleagues, by applying machine learning to multiple gene expression datasets, identified three clusters of patients with IPF with distinct clinical features and survival ( 8 ). Patients in different clusters demonstrated activation of different underlying biological pathways, including immune system response and metabolic changes that could potentially be modulated therapeutically ( 8 ).…”
Section: Pathway-driven Therapymentioning
confidence: 99%
“…Recently, Kraven and colleagues, by applying machine learning to multiple gene expression datasets, identified three clusters of patients with IPF with distinct clinical features and survival ( 8 ). Patients in different clusters demonstrated activation of different underlying biological pathways, including immune system response and metabolic changes that could potentially be modulated therapeutically ( 8 ). Precision medicine trials will be necessary to ensure that potential beneficial effects of drugs in specific endotypes are not overlooked because of heterogeneous effects in an unselected population.…”
Section: Pathway-driven Therapymentioning
confidence: 99%
“…identified a cilium associated subtype and a fatty acid metabolism one [ 43 ], but the expression of immune related genes or the associated cell types was not reported. Using blood transcriptomics, Kraven et al described three clusters of IPF patients, one of them enriched in immune response genes [ 44 ]. Additionally, Herazo-Maya JD et al identified a 52 gene signature on PBMCs that stratified patients with different disease outcomes [ 45 , 46 ], and an increase of peripheral blood monocytes has been associated with poor prognosis [ 47 ].…”
Section: Previous Studiesmentioning
confidence: 99%